Pengaruh Sertifikasi Halal terhadap Loyalitas Konsumen: Analisis Bibliometrik dan Tinjauan Literatur Sistematis (SLR) dalam Industri Makanan - Muhamad Alfian Sahrovi Ade Hanafi; Romi Faslah (CV. ITTC INDONESIA, 2025)
This study examines the impact of halal certification on consumer loyalty within the food and beverage industry through a bibliometric analysis approach. The dataset consists of 49 selected scholarly articles retrieved from the Scopus database, spanning the years 2015 to 2025. The research methodology combines a systematic literature review guided by the PRISMA framework with bibliometric analysis conducted using VOSviewer software, enabling the mapping of publication trends, collaborations among authors and institutions, as well as dominant keywords. Findings reveal that halal certification exerts a significant positive effect on enhancing consumer loyalty, primarily by fostering increased trust in product quality and safety. The study also identifies consumer trust as a moderating variable that strengthens the link between halal certification and loyalty. Furthermore, halal certification's influence extends beyond Muslim consumers, gaining recognition among non-Muslim customers as well. Nonetheless, certain studies report insignificant effects, which appear to be influenced by cultural and pricing factors. These results offer a more comprehensive understanding of the dynamics between halal certification and consumer loyalty in the global marketplace and highlight avenues for future research development.